Narratability of Knowing and Being: The Ontic Role of Materia Poetica in the Post-Mechanical Age (Journal of Education and Development, 2020)
The realm of mystery of matter that has long inspired creative minds has been broken by runaway complexification of life into fragments tossed around in voids of ‘total presence’. Apart from notable exceptions, the origin and actuality of the material condition of humans remain hidden from view by layers of ‘neo-baroque’ allegories framing narratives of the post-mechanical age. It is argued that resurrection of the ontic role of encounters with material reality may restore what has always served as an indispensable source of personal identity and life-sustaining narratives. It is also a means to fostering narrative novelty in the process of instilling timely attitudes and competences, with a view to ensuring that every individual can effectively engage with materiality of their presence and build upon its appreciation and on any inspiration it can offer, at the pace and level of accomplishment matching their personal ability and circumstances. It is this grounding of knowing and being that offers the promise of a bottom up transition to citizenship in a shared Common in which the key measure of value rests with promoting personal independence and social emancipation! What are the key stages of ‘allegorisation’ of narrativity and literary narratives in particular leading to the meta-modern present? What is the fate of materia poetica? The model of curriculum and competence development - grounded in object based, project driven, personal ownership of knowing, and amplifying the tutor-learner component at the expense of top down ‘talk and chalk’ - recently developed to take higher education into the digital age may be instrumental in delivering such objectives, and prove to be particularly relevant post-Covid 19.